226k views
1 vote
3x^+7x-6 factor completely

User Jodimoro
by
5.0k points

1 Answer

2 votes

The factor for given equation
3x^2+7x-6 is (3x-2) and (x+3).

Explanation:

To find the factors of the equation,

1) Multiply the coefficient of the
x^2 and the constant value.

⇒3×(-6)= -18.

2) Now find two numbers that can result is in -18 while multiplying and 7 (middle term or coefficient of x) while adding.

⇒9 × (-2) = -18.

9+(-2)= 7.

Now spit the equation as
3x^2+9x-2x-6.

=
(3x^2+9x)-(2x-6).

=3x(x+3) - 2(x+3).

=(x+3)(3x-2). (by taking out the common term x+3)

The factor for given equation
3x^2+7x-6 is (3x-2) and (x+3).